The more-individuals hypothesis revisited: the role of community abundance in species richness regulation and the productivity-diversity relationship - Storch, David; Bohdalková, Eliška; Okie, Jordan (Ecology letters, 2018)
Species richness increases with energy availability, yet there is little consensus as to the exact processes driving this species-energy relationship. The most straightforward explanation is the more-individuals hypothesis (MIH). It states that higher energy availability promotes a higher total number of individuals in a community, which consequently increases species richness by allowing for a greater number of species with viable populations. Empirical support for the MIH is mixed, partially due to the lack of proper formalisation of the MIH and consequent confusion as to its exact predictions. Here, we review the evidence of the MIH and evaluate the reliability of various predictions that have been tested. There is only limited evidence that spatial variation in species richness is driven by variation in the total number of individuals. There are also problems with measures of energy availability, with scale-dependence, and with the direction of causality, as the total number of individuals may sometimes itself be driven by the number of species. However, even in such a case the total number of individuals may be involved in diversity regulation. We propose a formal theory that encompasses these processes, clarifying how the different factors affecting diversity dynamics can be disentangled.
Keywords: Biodiversity; Reproducibility of Results; latitudinal diversity gradient; speciation; Population Dynamics; biodiverzita; diversity equilibria; biodiversity patterns; extinction; populační dynamika; environmental productivity; climate; reprodukovatelnost výsledků; species-energy relationship; Abundance